Early-Middle Pleistocene Beheading of the River Thames - Whiteman, Colin; Rose, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1997)
ABSTRACTThis paper marks the centenary of the first of three articles by W.M. Davis on the beheading of the Thames, beginning with a statement of his capture hypothesis in 1895 and concluding with attempts to explain anomalous misfit streams in 1899 and 1909. It discusses Davis's classic thesis of river capture by slow, long-term landscape evolution and his apparent reluctance to accept the fact of rapid Quaternary climate change. In contrast, recent work based on lithostratigraphy, biostratigraphy and morphostratigraphy emphasises the dynamism of the Quaternary Period and its influence on river capture. Possible mechanisms for the beheading of the Thames, tectonism, glacial erosion and conventional Davisian river capture, and the timing of the event, are discussed. In conclusion, the paper summarises known and unknown components of the problem of the beheading of the Thames, and discusses the extent of Davis's influence on later Thames studies.